2011
DOI: 10.1128/jb.01186-10
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Regulation of Histidine Kinases Governing Biofilm Formation inBacillus subtilis

Abstract: Bacillus subtilis is able to form architecturally complex biofilms on solid medium due to the production of an extracellular matrix. A master regulator that controls the expression of the genes involved in matrix synthesis is Spo0A, which is activated by phosphorylation via a phosphorelay involving multiple histidine kinases. Here we report that four kinases, KinA, KinB, KinC, and KinD, help govern biofilm formation but that their contributions are partially masked by redundancy. We show that the kinases fall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 24 publications
2
99
1
Order By: Relevance
“…Second, using the undomesticated strain, we confirmed that the biofilm formation is dependent on phosphorelay (Fig. 2a, b) as reported by McLoon et al (2011). For quantitative assay of biofilm formation, we measured expression levels of the PtapA-lacZ construct in MSgg medium and found that the reporter activities were significantly lower in the spo0F, spo0B or spo0A mutants than those in the WT strain (Fig.…”
Section: Resultssupporting
confidence: 49%
“…Second, using the undomesticated strain, we confirmed that the biofilm formation is dependent on phosphorelay (Fig. 2a, b) as reported by McLoon et al (2011). For quantitative assay of biofilm formation, we measured expression levels of the PtapA-lacZ construct in MSgg medium and found that the reporter activities were significantly lower in the spo0F, spo0B or spo0A mutants than those in the WT strain (Fig.…”
Section: Resultssupporting
confidence: 49%
“…The kinC mutant phenotype (Fig. 2a, b) appears strikingly different to what has been published by several groups (Ló pez et al, 2009a;McLoon et al, 2011). Furthermore, we have never detected early sporulation in a kinC mutant.…”
Section: Connection Of Kinc To Flotillins and Potassium Leakage In Bacontrasting
confidence: 51%
“…KinA contains three cytosolic PerArnt-Sim (PAS) domains that apparently sense starvation signals, but the identity of this signal is unknown. 12 In contrast, KinC and KinD appear to have a role in initiating the transition from exponential growth to stationary phase by generating low levels of Spo0A$ P. 6,13 KinC is activated in response to potassium membrane leakage and this activation depends on a single cytosolic PAS sensory domain. 14 KinD has been shown to delay the onset of sporulation 15 and has been proposed to act as a phosphatase under certain conditions, which regulates the level of Spo0A$ P. Its signal has been unidentified as of yet.…”
Section: Introductionmentioning
confidence: 99%